2018
DOI: 10.1002/wcc.511
|View full text |Cite
|
Sign up to set email alerts
|

Observation‐based detection and attribution of 21st century climate change

Abstract: The beginning of the 21st century has been widely designated a “global warming hiatus” or “pause” or “slowdown” because the rate of change of global surface temperature is a factor of two to three smaller than in the last half of the twentieth century. Indeed, observed global surface temperature (shown as black symbols in the top panel) warmed minimally. The rate of change of global surface temperature (shown as black symbols in the second panel) reached its lowest value in the 12‐year interval centered on 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 79 publications
(169 reference statements)
1
12
0
Order By: Relevance
“…In that hemisphere the solar variability shows the second strongest observed effect on the southern hemisphere temperature, similar to ENSO on seasonal time scales, and about a quarter of the anthropogenic influence. A similar underestimation of solar variability in models was pointed out by Lean (2018).…”
Section: Summary and Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In that hemisphere the solar variability shows the second strongest observed effect on the southern hemisphere temperature, similar to ENSO on seasonal time scales, and about a quarter of the anthropogenic influence. A similar underestimation of solar variability in models was pointed out by Lean (2018).…”
Section: Summary and Discussionsupporting
confidence: 77%
“…The current set of climate models (CMIP5) are tuned (Golaz et al, 2013;Stevens, 2015;Suzuki et al, 2013) to reproduce reasonably well the past climate variability, including short-term cooling by volcanic forcing. It has been suggested that the models' cooling response to volcanic and anthropogenic aerosols may have been overestimated (Canty et al, 2013;Driscoll et al, 2012;Lean, 2018;Marotzke & Forster, 2015;PAGES 2k Consortium, 2019;Sato et al, 2018). While it has been shown that models fail to capture the dynamical response following volcanic eruptions (Driscoll et al, 2012), others suggest that the overestimate might be due to a too strong radiative forcing (Marotzke & Forster, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. 67,68 and Refs. 69,70 quantify the contribution of tropical Pacific variability to GBST using multiple linear regression.…”
Section: Contributions Of Different Effects To the Observed And Modelmentioning
confidence: 99%
“…In regression-based approaches (Folland et al 2018;Foster and Rahmstorf 2011;Hu and Fedorov 2017;Johansson et al 2015;Lean 2018;Rypdal 2018;Saenko et al 2016;Schmidt et al 2014) the observed GMST, or its rate of change, is modelled by a number of predictors that are linearly combined. These studies differ in which predictors they include, whether the predictors are filtered, for example with a long-memory response (Rypdal 2018), an e-folding response profile (Folland et al 2018), or by using a mixedlayer model (e.g., Thompson et al 2008), and the temporal resolution of the predictors, i.e., monthly or annual.…”
Section: Comparison Of Methods To Quantify the Pacific Imprint On Gmstmentioning
confidence: 99%